Prediction of Road Noise Caused by a Tyre in a Passenger Car Based on Transfer Path Analysis and Vibro-Acoustic Reciprocity - Hwang, SungWook; Kim, YungIn; Park, JongHo; Lee, SangKwon (Asian Journal of Chemistry, 2013)
The quantification of road noise is a challenging issue in vehicle noise-vibration-harshness (NVH) due to the extremely complicated transfer paths of road noise as well as the difficulty in identifying the input force experimentally from tyre-road interactions. The noise caused by tyres is divided into road noise and pattern noise. Although pattern noise is the result of the tyre's pattern shape, in which the frequency band is >500 Hz, road noise involves interactions between the tyre and vehicle body. This paper reports the quantitative analysis of road noise caused by interactions between the tyre and road parameters. The chassis dynamometer, which was equipped with a 10 mm × 10 mm square cleat in the semi-anechoic chamber, was used to identify road noise and the tyre spindle forces were measured using a load cell. The vibro-acoustic transfer function between the ear position and wheel center was measured using the vibro-acoustic reciprocity method.